Tracking and synchronization control strategy of vehicle dual-motor steer-by-wire system via super-twisting SOSMC and MDCS. (15th January 2023) - Zou, Songchun; Zhao, Wanzhong; Wang, Chunyan
Highlights: A novel vehicle dual-motor steer-by-wire system is presented. An angle tracking controller via super-twisting SOSMC is designed to improve the tracking performance. A mean deviation coupling structure (MDCS) is proposed to enhance the synchronization performance. A synchronization control strategy based on MDCS and super-twisting SOSMC algorithm is proposed. The simulation and experimental results verify the effectiveness of the proposed control strategy. Abstract: This paper proposes a novel vehicle dual-motor steer-by-wire (SBW) system to improve the reliability and safety of traditional SBW system. However, the dual-motor SBW system is a strongly coupled, nonlinear and multivariable system, whose biggest challenge is the tracking and synchronization control. In order to improve the tracking and synchronization control performance of dual-motor SBW system, a tracking and synchronization control strategy of vehicle dual-motor SBW system via super-twisting second-order sliding mode control (SOSMC) and mean deviation coupling structure (MDCS) is proposed. Firstly, the steering motor model, rack and pinion model and vehicle dynamics model are established. Then, the angle tracking controller based on super-twisting SOSMC is designed to ensure the robustness and tracking performance of each motor. Next, the MDCS and the angle synchronization controller based on super-twisting SOSMC are proposed to compensate the synchronization error between dual-motor caused by mismatched driving force, external interference and parameter uncertainty. Finally, the simulation analysis is carried out by using Carsim/Simulink and the hardware-in-the-loop experiment is implemented based on the dual-motor experimental platform. The simulation and experimental results verify the effectiveness of the proposed control strategy.